Analisis Proses Transitivitas: Analisis Wacana Kritis Berbasis Korpus pada Judul-Judul Berita Surat Kabar Inggris dan Amerika Serikat - Oktaviani, Fatmala Sari (Jurnal Penerjemahan, 2024)
This study examines the representation of the Rohingya crisis in media discourse through the application of Critical Discourse Analysis (CDA) and Systemic Functional Linguistics (SFL), specifically focusing on the transitivity model to analyze the construction of newspaper headlines. Using a corpus-based approach, this research analyzes 100 headlines from the newspapers of United Kingdom and the United States published in 2017, drawn from the News on the Web (NOW) corpus. The analysis reveals that material processes are predominant in both the US and UK corpora, portraying the Rohingya as passive victims reacting to external aggression, thereby emphasizing the urgency of the crisis. Verbal processes are equally distributed across the corpora, highlighting influential figures such as political leaders and humanitarian organizations, and shaping the narrative through direct speech or reported dialogue. Relational processes, which assign attributes to participants, are more prevalent in the US corpus, where the focus is on the violence and prejudice faced by the Rohingya. In contrast, the UK corpus predominantly emphasizes their victimhood. These findings illustrate distinct media portrayals of the crisis, reflecting differing narrative strategies and political stances in the US and UK media.